Which laboratory test can be chosen for diagnosis and follow-up of rheumatic diseases by physicians? [Hekimler romatizmal hastaliklarin tani ve takibinde hangi laboratuvar testlerini seçiyorlar?] - (:unkn) unknown (My University, 2009)
Laboratory tests are widely used for diagnosis and follow-up of the rheumatic diseases. Most of these are not specific, especially used for prove the diagnosis. The aim of this study is to define laboratory tests that are used to diagnose rheumatic disorders by physicians in physical medicine and rehabilitation (PMR), internal medicine/rheumatology department. A total of 138 physicians both resident and specialist from PMR (73.9%) and internal medicine (26.1%) department participated into the study. The physicians were asked which laboratory tests they mostly use for the diagnosis and follow up of osteoarthritis, rheumatoid arthritis, ankylosing spondylitis and fibromyalgia syndrome. We found that erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are mostly used for diagnosis of these diseases (p< 0.05). In addition, 90-95% of physicans were chosen to know rheumatoid factor for diagnosis of rheumatoid arthritis. Residents need more laboratory tests to diagnose osteoarthritis and fibromyalgia syndrome when compared to specialists (p< 0.001). While the laboratory tests were ordered in the assessment of a rheumatic disease, physicians should consider if these tests provide optimal benefit and contribution for diagnosis and follow-up of the diseases. However, physicians should avoid ordering unnecessary tests for diagnosis and follow-up of the rheumatic disease. Copyright © 2009 by Türk Tibbi Rehabilitasyon Kurumu Derneǧi.
Keywords: Arthritis, rheumatoid; Fibromyalgia; Osteoarthritis; Rheumatic diseases